Evidence on the Relationship Between Emotional Intelligence and Risk Behavior: A Systematic and Meta-Analytic Review - Sánchez-López, María T.; Fernández-Berrocal, Pablo; Gómez-Leal, Raquel; Megías-Robles, Alberto (Frontiers in Psychology, 2022)
The aim of the present study was to carry out a qualitative and quantitative synthesis of the existing literature studying the relationship between emotional intelligence and risk behaviour. We conducted a systematic review and meta-analysis of the scientific evidence available relating both constructs. Particular attention was paid to identifying possible differences in this relationship as a function of the different conceptualizations of EI and the risk domain. The study was conducted following the Cochrane and PRISMA guidelines. Our results revealed a significant negative relationship between EI and health-related risk behaviours. However, this relationship was not observed in other risk domains such as finance and gambling. The relationship between EI and risk behaviour differed according to the risk domain studied, which supports the notion that risk is a domain-specific construct. The results associated with the health-related risk behaviours are consistent with existing literature about the positive impact of emotional abilities on the health domain. A more complete understanding of the emotional mechanisms that underlie risk behaviour could help to establish action guidelines and improve programmes to prevent and reduce the negative effects of risk behaviour on our society.